Nickel nanoparticles embedded in porous carbon nanofibers and its electrochemical properties. (8th May 2020) - Bai, Zhongxiong; Liu, Shucheng; Chen, Ping; Cheng, Guojie; Wu, Guangyao; Li, Han; Liu, Yi
Abstract: Flexible porous carbon nanofibers containing nickel nanoparticles were synthesized by direct carbonization of electrospun Ni-MOFs/polyacrylonitrile fibers. The as-synthesized composite nanofibers were employed as binder-free electrodes, and exhibit high specific capacitance (up 672 F g −1 at current density of 2 A g −1 ) and superior rate capability (57% capacitance retention from current density of 2–10 A g −1 ), which may be attributed to their binder-free nature, unique one-dimensional (1D) structure and highly dispersed electrochemically active nickel nanoparticles. Furthermore, a symmetric supercapacitor was assembled using the fiber electrodes in 6 M KOH, and the energy density of 17.8 Wh kg −1 was achieved in a potential window of 1.5 V. This self-standing fiber with abundant mesopores and macropores is expected to become a promising electrode material for high-performance supercapacitors.